The Utilization of Cassava and Sorghum Flours as A Staple Food in Indonesia - Gunawan, Setiyo; Aparamarta, Hakun Wirawasista; Darmawan, Raden; Qadariyah, Lailatul; Kuswandi, Kuswandi; Istianah, Nur (IPTEK Journal of Proceedings Series, 2018)
Indonesia has high a demand level of wheat flour for both the industrial and households sectors, such as bread industry. Wheat flour is the dominant composition of bread, however it is the source of gluten which may promote celiac disease (CD). The lifetime obedience to the gluten-free diet is the only treatment for this disease. The finding of a new material in order to obtain gluten-free product is an important topic. Furthermore, Indonesia is a tropical region that is rich in natural resources, such as cassava (Manihot esculenta) and Sorghum (Sorghum-bicolor (L) Moech). Fermentation was used to improve nutritional content of sorghum flour and cassava flour, resulting modified cassava flour (mocaf) and modified sorghum flour (mosof), respectively. A strategy for utilization of cassava in production of mocaf was demonstrated. Mocaf flour can be produced by fermentation use L. plantarum, S. cereviseae, and R. oryzae that are cheap and non pathogenic to increase the levels of protein and decrease the levels of cyanide acid in the mocaf flour. This work has also shown that lactid acid is produced as by-product during the fermentation.